2016
DOI: 10.1186/s13018-016-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of erythropoietin on biomechanical properties of the Achilles tendon during the healing process: an experimental study

Abstract: BackgroundThe aim of this study was to examine the potential biomechanical and histological benefits of systemic erythropoietin administration during the healing of Achilles tendon injury in a rat experimental model.MethodsEighty Sprague-Dawley female rats were included in this study. Animals were randomly assigned into two groups with 40 animals in each: erythropoietin group and control group. Then each group was further divided into four subgroups corresponding to four time points with 10 animals in each. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
4
1
1
Order By: Relevance
“…Journal of Orthopaedic Surgery 27 (2) et al on the effects of EPO on the Achilles tendon investigated at 3 weeks, the EPO-treated group showed worse results than did the control group when vascular formation was examined. 18 This result is inconsistent with our findings. The reason for this conflict may be related to their design, because they observed that the control group also showed a decrease in vascular formation over time, but it was not statistically significant.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Journal of Orthopaedic Surgery 27 (2) et al on the effects of EPO on the Achilles tendon investigated at 3 weeks, the EPO-treated group showed worse results than did the control group when vascular formation was examined. 18 This result is inconsistent with our findings. The reason for this conflict may be related to their design, because they observed that the control group also showed a decrease in vascular formation over time, but it was not statistically significant.…”
contrasting
confidence: 99%
“…In an Achilles tendon repair model, Bilal et al found no effect on tendon healing with systemic EPO (500 U/kg) administration either histopathologically or biomechanically. 18 In our study, we found better results biomechanically in the early systemic group (10th day), and histopathologically, we found better results in the late systemic and the late local groups compared to the late control group (28th day). This result could be related to the differences between the rotator cuff and Achilles tendon structures.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…En otro estudio, al comparar dos técnicas de intervención: el uso de tornillos absorbibles versus tornillos metálicos para lesiones por sindesmosis tibioperoneales distal, resultó similar en cuanto a tiempos de reparación, a diferencia de las reacciones de cuerpo extraño y las reoperaciones [44]. Existen estudios que demuestran la disminución de los tiempos de reparación de las heridas con la aplicación de eritropoyetina, pero con la cual no se ha demostrado eficacia en lesiones tendinosas [45]. Y en otros casos, el uso de productos sanguíneos autólogos, como los geles de concentrados plaquetarios autólogos, sirven para disminuir el tiempo de reparación de las lesiones osteocondrales, musculares, tendinosas y ligamentarios, pero sin efecto en grandes articulaciones [46].…”
Section: Tiempo De Reparación De Las Lesionesunclassified